EFFECTS OF INDIGENOUS GAMES–BASED PHYSICAL EDUCATION ON PHYSICAL PERFORMANCE, NEUROMECHANICAL EFFICIENCY, AND PSYCHOSOCIAL OUTCOMES IN TRIBAL SCHOOL CHILDREN: A RANDOMIZED CONTROLLED TRIAL - S, Deepak J; Harigaran, D (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Indigenous games represent culturally embedded physical activities with potential benefits for holistic development; however, experimental evidence in school-based settings remains limited. This randomized controlled trial examined the effects of an eight-week indigenous games-based physical education programme on physical performance, neuromechanical efficiency, and psychosocial outcomes in tribal school children. The participants (11-15 years old) were randomly divided into 48 experimental (indigenous games) and control (conventional physical education) groups. The intervention was conducted three times per week for eight weeks. Pre- and post-intervention measures of physical performance (30 m sprint, agility, standing broad jump, and estimated VO2 max), neuromechanical variables (reactive strength index, ground contact time, and change-of-direction deficit), and psychosocial outcome (social cohesion, motivation, and enjoyment) were measured. The covariance analysis indicated that there were significant group x time group effects in favour of the experimental group in all the variables (p < 0.001), and the effect sizes (n2p) are very large (0.27-0.35). The experimental group showed significant changes in sprint performance (−7.0%), agility (−8.1%), lower-limb power (+11.3%), and aerobic capacity (+14.1%). Neuromechanical changes involved a more reactive strength index and less ground contact time, which showed more efficiency in the stretch-shortening cycle. Psychosocial measures demonstrated significant improvements in social cohesion and intrinsic motivation. These results indicate that indigenous games offer a culturally pertinent and scientifically sound strategy of enhancing multidimensional developmental outcomes of tribal youth in school-based physical education.